Embarrassing Product, Image Type, and Personal Pronoun: The Mediating Effect of Body Imagery - Ye, Shenghong; Yan, Haoyun; Lin, Zhengyu; Huang, Zan (Frontiers in Psychology, 2022)
Consumers often feel embarrassed when buying products like condoms, hemorrhoid cream, and beriberi cream in crowded pharmacies. There is an interesting phenomenon in life: Some beriberi creams use the images of "a real foot", while others use the images of "a cartoon foot". Imagine if a young woman needed to go to a retail store for beriberi cream that would embarrass her, she would choose a "real foot image" or a "cartoon foot image" beriberi cream? It has been shown that the embarrassment of these products has a strong negative impact on consumer buying behavior. Previous researches have explored how changing packaging elements of embarrassing products (e.g., color/design/image placement) can effectively reduce consumer embarrassment. However, few have examined the impact of different image types of embarrassing product packaging (artificial vs. natural) with embarrassment. Therefore, this research explores the effect of image types (artificial vs. natural) on consumers' willingness to purchase embarrassing products and reveals the mechanisms of the underlying effects. The results show that natural images can lead to lower purchase intention of embarrassing products when the advertisement is in the first-person pronouns due to the mediating role played by negative body imagery. However, there is no significant difference in purchase intention between different image types in the third-person pronouns. Finally, this paper discusses the contributions and limitations.